Research practice for cultural studies : ethnographic methods and lived cultures - Gray, Ann, 1946- (London ; Thousand Oaks, Calif. : SAGE, 2003)
How is culture 'lived'? What are the best ways of investigating cultural life? This book offers practical guidance for researching cultural studies.
Part I: Ethnographic Methods: 1. Grasping Lived Cultures -- 2. Articulating Experience -- 3. Imagined Communities: The Spectacular and the Ordinary -- 4. A Question of Research. Part II: The Research Process -- 5. Locating Instances and Generating Material -- 6. I Want to Tell You a Story -- 7. Typing in the Texts -- 8. Strategies and Tactics in Analysis -- 9. Writing -- 10. Sources of Knowledge and Ways of Knowing.
Includes bibliographical references (pages 191-198) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Print version record.
Keywords: Culture -- Research; Culture -- Study and teaching; Social sciences -- Research -- Methodology; Ethnology -- Methodology; Culture -- Étude et enseignement; Sciences sociales -- Recherche -- Méthodologie.; Ethnologie -- Méthodologie.; SOCIAL SCIENCE -- Research; SOCIAL SCIENCE -- Methodology; Culture -- Research; Culture -- Study and teaching; Ethnology -- Methodology; Social sciences -- Research -- Methodology; Sociaal-wetenschappelijk onderzoek; Methodologie; Etnografie; Cultural studies -- Social research & statistics